2149. Performance of a Gradient Diffusion Method (Etest®) on Mueller–Hinton Agar with Sheep Blood for Aerococcus urinae Antimicrobial Susceptibility Testing - Berteau, Tammy (Open Forum Infect Dis, 2019)
BACKGROUND: Aerococcus urinae is frequently identified by MALDI-TOF in urinary specimens. It is generally susceptible to β-lactams, but its susceptibility pattern to fluoroquinolones (FQ) remains unpredictable. The goal of this study was to evaluate the performance of the gradient diffusion method (Etest®) to determine FQ susceptibility compared with broth microdilution (BMD) and agar dilution (AD). METHODS: Prospectively collected isolates of A. urinae from urinary tract specimens originating from 5 hospitals in Quebec city and Montreal were identified by MALDI-TOF (Vitek-MS). All isolates were tested using BMD according to CLSI guidelines, and also with Etest® strips on MH agar w/ 5% sheep blood. Isolates showing trailing, insufficient growth or discordance between both methods were further tested by agar dilution (MH agar w/5% horse blood + β-NAD) according to EUCAST guidelines. Breakpoints were interpreted using CLSI M45-A3. Combined results of BMD and AD were then compared with Etest. RESULTS: Of the 207 isolates of A. urinae tested, 37 showed trailing (17,8%) and 19 (9,2%) insufficient growth with the BMD method and were retested using AD. Moreover, 38 isolates (ciprofloxacin) and 13 isolates (levofloxacin) showed either lack of categorical or essential agreement between Etest and BMD and were also retested using AD to arbitrate discrepancies. Susceptibility profiles combining BMD and AD are presented in Table 1. As suggested in EUCAST guidelines, readings were much clearer and growth was better with AD compared with BMD. The categorical agreement of the Etest® with BMD+AD was 95% for ciprofloxacin and 97% for levofloxacin. Essential agreement was 95% for ciprofloxacin and 97% for levofloxacin. No very major errors were identified. Two major errors were identified for levofloxacin (1,2%) and one for ciprofloxacin (0.6%). CONCLUSION: Gradient diffusion method using Etest® strips on MH agar w/ sheep blood is a valid method to determine susceptibility to FQ for urinary tract isolates. As a reference method, AD provides clearer endpoints and better growth than BMD for FQ susceptibility testing. [Image: see text] DISCLOSURES: All authors: No reported disclosures.